Thematischer gehalt und dramatisches geschehen im platonisczen dialog. Sokrates und die "umwendung der ganzen seele" oder zur audiovisualität der platonischen dialoge - Königshausen, Johann-Heinrich (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2012)
During Plato’s lifetime it was a very common thing to read loud circulating writings or let them be read by others. It is said that Plato initially wanted to write tragedies. And he undoubtedly created dramas, which are performed in the mind of the reader, listener and viewer. Therefore, the addressee of a Platonic dialogue is, in principle, not only a listener, but also a spectator. We can hear what is being said by an actor (a character) and we can see his acting; and if the stage is too far away, then distant, no longer visible events are “told” to the viewers. Thus, as for the philosophical reading of the Greek classics, one should not only read the written texts, but also watch what is being shown by the characters’ play (arguments).